Mapping the BDA20 Gene to BTAX - Stafuzza, N. B. [UNESP]; Kata, S.; Womack, J. E.; Amaral, M. E. J. [UNESP] (Karger, 2008)
The lipocalin family is a large group of proteins that exhibits great structural and functional variation both within and among species, including a significant number of animal-derived aeroallergens, such as the bovine BDA20 (major cow dander allergen). This protein is classified as an occupational allergen causing asthma and other work-related allergic disorders among dairy farmers. Using a somatic cell panel the BDA20 gene was assigned to the bovine X chromosome (BTAX) with a significant concordant value of 97% to the previously mapped reference marker MAF45. A radiation hybrid (RH) mapping approach confirmed the assignment of BDA20 to BTAX. Two-point LOD scores showed that BDA20 is linked to XBM451 with a LOD score of 22.1 for a 0 value of 0.03.
Keywords: BTAX; major cow dander allergen; X chromosome; BDA20